Peranan Guru dalam Peningkatan Pelaksanaan P5-PPRA bagi Siswa MIN 1 Pati - Anas, Muhammad Choirul (Sekolah Tinggi Agama Islam Pati, 2023)
The main challenges in implementing P5-PPRA (Pancasila Student Profile Strengthening Project and Rahmatan Lil Alamin Student Profile) in madrasahs include teachers' limited competence in designing collaborative projects and low student participation. This study aims to analyze the role of teachers in enhancing the implementation of P5-PPRA at MIN 1 Pati. Using a qualitative method, this research involved teachers and students of the Madrasah Ibtidaiyah (Islamic Elementary School) as subjects. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed thematically. The results indicate that teachers play a significant role in improving the implementation of P5-PPRA through competency development, motivation, and student monitoring. Therefore, this study recommends that teachers enhance their abilities in developing P5-PPRA and increase student engagement in P5-PPRA activities. These findings underscore the importance of integrating religious and national values in character education within madrasah environments.